EFFECT OF BOLUS SIZE ON DEGLUTITION AND ESOPHAGEAL TRANSIT IN HEALTHY DOGS. Issue 4 (14th April 2016) - Cheney, Diane M.; Marks, Stanley L.; Pollard, Rachel E.
Abstract : Contrast videofluoroscopy is the gold standard procedure for evaluating dysphagia in humans, but quantitative measures vary depending on bolus size and consistency. We hypothesized that quantitative measures made during videofluoroscopy of swallowing in dogs would differ between bolus sizes and consistencies. Ten healthy adult dogs were enrolled a prospective, crossover experimental study and underwent contrast videofluoroscopy while swallowing liquid (5, 10, and 15 ml) and canned food (3, 8, and 12 g) boluses. Maximum pharyngeal contraction occurred significantly later with medium solid boluses than with medium liquid boluses, with a mean difference of 0.021 s (adjusted P = 0.042). Upper esophageal sphincter opening occurred significantly earlier with large solid boluses than with medium solid boluses, with a mean difference of 0.018 s (adjusted P = 0.025). Thoracic esophageal transit time was significantly longer with small solid boluses than with small liquid boluses, with a mean difference of 0.68 s (adjusted P = 0.004). Odds of primary esophageal peristalsis occurring were significantly (18.5 times) higher with large solid vs. large liquid boluses (adjusted P = 0.031). No other statistical comparisons reached significance. Based on these results, we recommend a standardized approach to videofluoscopy in dogs with determination of quantitative measures using medium liquid and soft food boluses to minimize effects of size. Furthermore, we conclude that measurements made on liquid swallows should not be directly compared to measurements made on soft food boluses.